Chauliocheilos saxatilis, a new genus and species of Hypoptopomatinae from rio Jequitinhonha basin, with a unique labial appendix (Teleostei: Loricariidae) - Martins, Fernanda de Oliveira [UNESP]; Andrade, Breno Neves de [UNESP]; Rosa, Alaina Cristine [UNESP]; Langeani Neto, Francisco [UNESP] (My University, 2014)
Chauliocheilos saxatilis, new genus and species, is described from headwater streams of the rio Itamarandiba, upper rio Jequitinhonha basin, southeastern Brazil. The new genus is diagnosed from all other Loricariidae members by having a unique labial appendix at laterodorsal portion of lower lip, associated to the proximal region of insertion of the maxillary barbel. From all Hypoptopomatinae genera, Chauliocheilos can be distinguished by having two additional series of lateral plates, one between the dorsal and mid-dorsal series, and the other between the mid-ventral and ventral series. In addition, the great number of lateral plates, the absence of the iris operculum, and the posterior dorsal-fin insertion contacting the neural spine of eighth vertebra, are other useful features to recognize the genus. The phylogenetic position of Chauliocheilos among the Hypoptopomatinae, as well as the morphology and possible functions of the labial appendix, are discussed.

Chauliocheilos saxatilis, um novo gênero e espécie de hipoptopomatíneo, é descrito de riachos de cabeceira do rio Itamarandiba, bacia do alto rio Jequitinhonha, sudeste do Brasil. O novo gênero é diagnosticado de todos os outros Loricariidae por ter um apêndice labial único na porção laterodorsal do lábio inferior, associado à região proximal de inserção do barbilhão maxilar. De todos os gêneros de Hypoptopomatinae, Chauliocheilos pode ser distinguido por apresentar duas séries adicionais de placas laterais, uma entre as séries dorsal e médio-dorsal e a outra entre as séries médio-ventral e ventral. Além disso, o grande número de placas laterais, a ausência do opérculo da íris e a inserção posterior da nadadeira dorsal contatando o espinho neural da oitava vértebra, são outras características importantes no reconhecimento do gênero. O posicionamento filogenético de Chauliocheilos entre os Hypoptopomatinae, assim como a morfologia e possíveis funções do apêndice labial, são discutidas.